Comment on ?Highly efficient and sustainable cationic polyvinyl chloride nanofibrous membranes for removal of E. coli and Cr (VI): Filtration and adsorption? - Chu K.H.; Hashim M.A.; Hayder G.; Bollinger J.-C. (Elsevier B.V., 2025)
This correspondence delves into deficiencies in the modeling work presented in a recent publication within this journal. It specifically asserts that (i) the authors employed flawed models for fitting adsorption data, and (ii) they neglected to take into account the conditions under which simplified models remain valid. ? 2024 Elsevier B.V.